Influence of Enzyme Concentration, Hydrolysis Duration, and Drying Temperature on the Production of Antioxidant-containing Peptide from Catfish (Clarias sp.) Gills - Masagus Muhammad Prima Putra; Winnen Wisnumurti; Nezar Helmi Athallah; Al Tarich Arasy Zaen; Aulia Rachma Sahura; Ustadi Ustadi (Diponegoro University, 2025)
Catfish gills are a potential raw material for producing protein hydrolysate with antioxidant activity. Protein hydrolysate was produced using crude papain enzyme in two stages. The first stage was to obtain the optimum enzyme concentration (w/w) including 1%, 2%, 3%, 4%, 5% and 6%, with 0% as a control, followed by the second stage to obtain the optimum hydrolysis duration for 24, 48, 72, and 96 hours, with 0 hour as a control. The supernatant containing protein hydrolysate was then dried using an oven at various temperatures, including 60, 70, and 80°C, for 48 hours to obtain catfish gill protein hydrolysate (CGH) powder. CGH was tested for degree of hydrolysis (DH) and antioxidants, including DPPH and ABTS. The highest antioxidant activity was obtained from 3% papain with DPPH and ABTS values of 85% and 9.57 µM TEAC, respectively. Further stage on the hydrolysis duration gave 48 hours as the optimal one, with antioxidant activity of 85.25 % for DPPH and 4.29 µM TEAC for ABTS. The oven-drying temperature concluded that CGH has stable antioxidant activity. The IC50 on antioxidant activity based on DPPH ranged from 1799.85 mg/L to 1749.50 mg/L (IC50 of ascorbic acid was 2.61 mg/L) and was included as very weak. Even though based on IC50, CGH has low antioxidant activity, the protein content was found to be high (56.86±1.51%), which could be a high-protein food additive.